Macro Shocks and Industrial Portfolio Responses: An Econometric Model for LDCs - Tybout, James; Bark, Taeho (The Review of Economics and Statistics, 1988)
A dynamic model of corporate balance sheet structures and net worth growth is fit to firm-level panel data from Uruguay. Basic findings are: (1) net income is very sensitive to financial costs and demand for output; (2) there is a direct proportionality between net income and net worth expansion; (3) firms absorb most short-run fluctuations in net worth via adjustments in assets, not debts; and (4) the interest elasticity of corporate demand for peso debt is very small. Inter alia, these results imply that rapid changes in the exchange rate have large effects on corporate sector leverage and liquidity. Copyright 1988 by MIT Press.